ANALISIS MANAJEMEN RISIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN MENGGUNAKAN METODE HIRARC PADA PEKERJAAN SEKSI CASTING - Rini Alfatiyah (SINTEK JURNAL: Jurnal Ilmiah Teknik Mesin, 2017)
PT. XYZ Serpong unit is a manufacturing company involved in the installation of a pipe that prioritizes Safety and Health (K3) in every work activity. To support the implementation of the Occupational Safety and Security Management System (SMK3), the investigation was conducted using Hazard Risk Assessment, Risk Assessment and Risk Control (HIRARC) in the Casting section. Possible dangers in 5 stages of work breaker at PT XYZ. is the process star rating, LPDC (Low Pressure Die Casting), shotblast, cutting and range. After conducting an investigation with Hazard Risk Assessment, Risk Assessment and Risk Assessment (HIRARC) in the category of major hazard risk stages, 60% were core processes, LPDC and cutting. Although the risk hazard category that may be accepted as much as 40% is the process of shooting and range.